Using sentiment analysis to study the relationship between subjective expression in financial reports and company performance - Zhong, Ni; Ren, JunBao (Frontiers in Psychology, 2022)
In recent years, with the development and progress of text information research in many aspects, it is basically unanimously found that the disclosure of non-financial information and qualitative information has a certain information increment function. Financial reports, including financial statements and other relevant information that should be disclosed in financial reports, are an important way to reflect accounting information such as the financial status, operating results, and cash flow of an enterprise. Faced with a large number of financial reports, readers often do not know where to start, and financial statements are prepared based on past transactions, which cannot fully reflect the past, present, and future economic conditions of the company. The widespread existence of information asymmetry and uncertainty makes the text mining of financial reports of great significance to the stakeholders of enterprises. Based on this, this paper takes financial reports as the research object and builds a research framework on the relationship between the subjective expression of financial reports and company performance. Through natural language processing technology, sentiment analysis, and other text mining technologies, it further quantifies the subjective expression of financial reports and introduces intermediaries. Variables, moderating variables, and control variables construct a multiple regression model. The empirical research shows that the underlying emotional tendencies in the subjective expressions of listed companies' financial reports have a substantial impact on the future development of enterprises. This paper provides ideas for further exploring the multi-dimensional relationship between financial report text information and company performance and has a certain role in enriching and improving the multi-dimensional relationship between financial reports and company performance. It is of great practical significance to help them make rational decisions and ensure the normal operation of the company and the preservation and appreciation of capital.